SOSIALISASI POLA ADAPTASI KEBIASAAN BARU MENGHADAPI PANDEMI COVID 19 - Rekho Adriadi; Titi Darmi; Ledyawati Ledyawati (Jurnal Abdimas Serawai, 2021)
: In early June the Indonesian government launched the concept of "Peace" with Covid-19 which was subsequently realized by the issuance of the "New Normal" policy in which the government allowed the community to do activities as usual but still paid attention to the Covid-19 protocol. The concept of "New Normal" which is now known as New Habit Adaptation has begun to be applied in areas with green zone status. Seluma Regency, Bengkulu Province has received the green zone predicate and can implement new habit adaptation policies in community activities, and it needs massive socialization to The community is included in the community of Padang Pelasan village, Air Periukan sub-district, Seluma Regency. The material for the socialization activities carried out is not far from the guidelines for healthy living according to the Covid-19 health protocol in order to adopt a new habitual adaptation pattern such as the Ministry of Health appeal and is considered quite successful. This can be seen from the enthusiastic participation of the community and accepting the team in carrying out activities. In addition, in the evaluation of activities, quite a number of people have started to become aware of health protocols such as the habit of wearing masks